Pengaruh Self Efficacy dan Lingkungan Kerja Terhadap Kinerja Pegawai di Dinas Komunikasi dan Informatika Kabupaten Pesisir Selatan - Tiara Mesriyani; Riri Mayliza (Universitas Kristen Indonesia Toraja, 2024)
This research aims: 1. To prove and analyze the effect of Self Efficacy on Employee Performance at Dinas Komunikasi dan Informatika Kabupaten Pesisir Selatan; 2. To prove and analyze the effect of the Work Environment on Employee Performance at Dinas Komunikasi dan informatika Kabupaten Pesisir Selatan. The method used in this research is quantitative method. The sample in this study were 34 respondents with the sampling technique used was total sampling. The data analysis technique starts based on the research instrument test, classical assumption test, multiple linear regression, and hypothesis testing. This study shows the results: 1. Self efficacy has a positive and significant effect on employee performance; 2. Work environment has no significant effect on employee performance.